Composition anisotropy compensation and magnetostriction of Co-doped Laves compounds Tb0.2Dy0.8−xPrxFe1.93 (0 ≤ x ≤ 0.40). (July 2018) - Li, F.; Liu, J.J.; Zhu, X.Y.; Shen, W.C.; Lin, L.L.; Du, J.; Si, P.Z.
Abstract: Alloys of Tb0.2 Dy0.8−x Prx (Fe0.8 Co0.2 )1.93 (0 ≤ x ≤ 0.40) are arc melted and investigated for structural, magnetic and magnetoelastic properties by means of X-ray diffraction (XRD), a vibrating sample magnetometer and a standard strain technique. The 20 at.% Co substitution for Fe is shown to enable the formation of the single Laves phase with a high Pr content up to x = 0.25. Experimental evidence for magnetocrystalline-anisotropy compensation between Pr 3+ and Dy 3+ ions is obtained in the Laves phase system. The easy magnetization direction (EMD) at room temperature rotates from <100> to <110> axis when x increases from 0 to 0.40. The linear anisotropic magnetostriction λ a (=λ|| –λ⊥ ) increases with increasing Pr content when x ≤ 0.25 ascribed to both the larger magnetostriction of PrFe2 than that of DyFe2 and the decrease of the resulted anisotropy due to compensation. The composition anisotropy compensation is found to be around x = 0.25, shifting to the Pr-rich side at room temperature as compared to the Co-free counterpart Tb0.2 Dy0.8−x Prx Fe1.93 system. The Tb0.2 Dy0.55 Pr0.25 (Fe0.8 Co0.2 )1.93 alloy has good magnetoelastic properties at room temperature, that is, a low anisotropy and a high low-field magnetostriction λ a ∼140 ppm at 1 kOe. Highlights: The easy magnetization direction is detected by XRD on magnetically oriented powders. EMD rotates from <100> to <110> axis with increasing Pr content. Evidence is obtained for anisotropy compensation between Dy 3+ and Pr 3+ ions. Co-substitution shifts the composition for anisotropy compensation to Pr-rich side.